The effect of spinel ferrites on the performance of lithium-sulfur batteries - Yong, Jim Khang Hai (2019)
Sulfur is an interesting cathode material for Lithium-ion battery as it provides a high specific capacity of 1675 ℎ −1. However, obstacles contributed by dissolution of cathode materials need to be overcome before we can fully utilize the benefits of sulfur as cathode material in the battery. Despite much efforts in introducing metal oxide as additives and hybrid structures, very little attention had been given to this large group of spinel metal oxide structure and the benefits it could offer. Here, some other spinel metal oxides ( 2 4, 2 4 and 2 4) had been explored as additives in the cathode of Lithium-Sulfur battery to prevent dissolution of polysulfides into the electrolytes. The initial specific capacity found for the three spinel oxides exceeded 900 ℎ −1 at 0.2C, which was significantly higher than most metal oxides. And the Coulombic Efficinecy were maintained at higher than 95% after 70th cycle. However, the total capacity loss was as great as 32.35% demonstrated by 2 4, followed by 26.42% ( 2 4) and (25.60%) ( 2 4) respectively, implying that dissolution of polysulfides still exists.